2007
DOI: 10.1118/1.2760426
|View full text |Cite
|
Sign up to set email alerts
|

SU‐FF‐I‐49: Daily Patient Dose From Kilo‐Voltage Cone‐Beam Computed Tomography: A Comparison Between XVI and OBI

Abstract: Purpose: To make a comprehensive set of absolute dose measurements from the X‐ray Volumetric Imager (XVI®, Elekta Medical Systems) and the On‐Board Imager (OBI®, Varian Medical Systems) on cylindrical phantoms using a calibrated ion chamber. Method and Materials: Two cylindrical (acrylic) phantoms with diameters of 18 cm (head phantom) and 30 cm (body phantom) were used for all measurements. Each phantom has a hole in the center and 2 cm below the phantom surface. For the XVI unit, the four manufacturer‐suppli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…CBCT imaging would be repeatedly applied to a patient during the IGRT treatment course for over 25 times in common. It raises a great concern that repeated CBCT scans deliver too much dose to the patient at 3 ∼ 5 cGy per scan and 90 ∼ 150 cGy if scanned daily for Varian on-board imager [4] and the isocenter doses ranged between 0.1 and 2.2 cGy per scan for the Elekta X-ray volumetric imager [5]. In addition, CBCT delivery dose from a Varian Trilogy accelerator was accurately investigated by Monte Carlo simulations and their results have shown that doses from a typical head and neck CBCT scan to eye, spinal cord, brain and bone could be up to 8 cGy, 6 cGy, 5 cGy and even 25 cGy, respectively for Varian on-board imager [6].…”
Section: Introductionmentioning
confidence: 99%
“…CBCT imaging would be repeatedly applied to a patient during the IGRT treatment course for over 25 times in common. It raises a great concern that repeated CBCT scans deliver too much dose to the patient at 3 ∼ 5 cGy per scan and 90 ∼ 150 cGy if scanned daily for Varian on-board imager [4] and the isocenter doses ranged between 0.1 and 2.2 cGy per scan for the Elekta X-ray volumetric imager [5]. In addition, CBCT delivery dose from a Varian Trilogy accelerator was accurately investigated by Monte Carlo simulations and their results have shown that doses from a typical head and neck CBCT scan to eye, spinal cord, brain and bone could be up to 8 cGy, 6 cGy, 5 cGy and even 25 cGy, respectively for Varian on-board imager [6].…”
Section: Introductionmentioning
confidence: 99%